SIMPLIFIKASI RITUAL HARAI DAN DIMENSI KULTURAL HOFSTEDE DALAM IKLAN FORTE VERSI SUMO - Bernard Realino Danu Kristianto; Rustono Farady Marta (Bricolage : Jurnal Magister Ilmu Komunikasi, 2019)
ABSTRACTThis research is entitled Simplification of Hit Ritual and Hofstede Cultural Dimensions in Sumo Version of Forte Ads. This study aims to understand the Harai Rituals in simplified Sumo rituals and Hofstede's cultural dimensions in FORTE cigarette product advertisements. The FORTE cigarette product is relatively new in the Indonesian market. This cigarette product originating from a Japanese company was launched by a local Indonesian company, PT Djarum. But in the advertisement, the product featured Sumo wrestlers who were squeezed by a frame which later revealed mighty tiny writing as the main FORTE cigarette slogan. In the discussion, it will be explained how Hofstede's dimensions of cultural cross are presented through the overall appearance of Forte's cigarette advertisements and products. The researcher concluded that the audio-visual work of Forte cigarette products in the form of advertisements was a simplification of the ritual of the Sumo sport for the purpose of product promotion and the duration of the ad itself. The Japanese cultural identity that appears in FORTE's cigarette advertisements through Sumo sports has the complexity of historical cultural dimensions which are full of meaning and philosophy.Keywords; Simplification, Harai, ritual, cultural, Hofstede, Forte.ABSTRAKPenelitian ini berjudul Simplifikasi Ritual Harai dan Dimensi Kultural Hofstede dalam Iklan Forte Versi Sumo. Penelitian ini bertujuan memahami Ritual Harai dalam ritual Sumo yang tersimplifikasi serta dimensi budaya Hofstede dalam iklan produk rokok FORTE. Adapun produk rokok FORTE ini tergolong baru di pasar Indonesia. Produk rokok yang berasal dari perusahaan Jepang ini diluncurkan oleh perusahaan lokal Indonesia, PT Djarum. Namun dalam penayangan iklannya, produk ini menampilkan pegulat Sumo yang terhimpit oleh frame yang kemudian memunculkan tulisan mighty tiny sebagai slogan utama rokok FORTE tersebut. Dalam pembahasan, akan dipaparkan bagaimana dimensi-dimensi lintas kultural Geert Hofstede dipaparkan melalui penampilan keseluruhan iklan dan produk rokok Forte. Peneliti mengambil kesimpulan bahwa karya audio visual produk rokok Forte yang berbentuk iklan merupakan simplifikasi ritual harai dalam olahraga Sumo demi tujuan promosi produk dan durasi iklan itu sendiri. Identitas budaya Jepang yang tampil dalam iklan rokok FORTE melalui olah raga Sumo memiliki kompleksitas dimensi kultural historis yang sarat makna dan filosofi.Kata kunci; Simplifikasi, ritual, Harai, kultural, Hofstede, Forte.